The Perceptions of a Student Teacher on Implementing Active Learning with Junior Cycle Students - Dunne, Sandra (TARA, 2021)
This article is a reflective analysis of one active learning methodology (i.e. a table quiz), and is part of a larger study. The motivating force for this study arose from the researcher’s desire to gauge a deeper understanding of the process, to improve their own practice.
Journal article
Keywords: Active Learning; Junior Cycle Reform; Motivation; Active learning; Motivation in education